Hospital financial performance under the prospective payment system by type of admission: psychiatric versus medical/surgical. - Freiman, M P (1990)
We performed detailed simulations of DRG-based payments to general hospitals for treatment of nonexempt psychiatric and medical/surgical patients under Medicare's prospective payment system (PPS). We then compared these results to calculated costs for the same patients. Hospitals without specialized psychiatric units tend to fare better financially on their psychiatric than on their medical/surgical caseloads, although the levels of gain for these two types of patients are correlated. Hospitals with nonexempt psychiatric units generally have similar rates of gain on psychiatric and medical/surgical patients. Comparing psychiatric treatment in "scatter-bed" sites with that provided in nonexempt units, the higher rate of gain under PPS for treatment in scatter beds results largely from shorter lengths of stay. We discuss hospital behavior and the relationships between treatment of psychiatric illness under DRG-based payment and its treatment in exempt psychiatric units, which are excluded from DRG-based payment.